Geolocators reveal variation and sex‐specific differences in the migratory strategies of a long‐distance migrant. (19th October 2021) - Bell, Fraser; Bearhop, Stuart; Briedis, Martins; El Harouchi, Myriam; Bell, Sophie C.; Castello, Joan; Burgess, Malcolm
Abstract : Songbird populations are in decline all over the world, and our understanding of the causal mechanisms remains surprisingly limited. It is important to identify the extent of individual variations in migratory behaviour to better understand species' ability to respond to environmental change. We describe the annual migratory behaviour of British breeding European Pied Flycatchers Ficedula hypoleuca by using light‐recording geolocators. During both autumn and spring migrations, individuals used previously unknown staging areas on the Iberian Peninsula and northern West Africa. Furthermore, partial sex‐specific segregation in the location of non‐breeding areas was observed within West Africa, with females located west of males. We also found sex‐based phenological differences, with females staying longer in non‐breeding areas and undertaking the spring Sahara Desert crossing later than males. Irrespective of sex, multiple use of the two predominant staging regions was identified during both migrations, with 63% of individuals stopping more than once in these regions. We also identified instances of migratory behaviours rarely documented in individually tracked songbirds. These include making daytime landfall during the Sahara crossing, and a case of a temporary retreat migration, with an individual aborting a spring Sahara crossing before making a second successful crossing 14 days later. Together, our results show variability in migratory behaviour both between sexes and between individuals. For Pied Flycatchers, such flexible migratory behaviour may increase their resilience to environmental change.